Effects of noise exposure of other people on aircraft noise tolerability using a reference point approach. (October 2016) - Phun, Veng Kheang; Hirata, Terumitsu; Yai, Tetsuo
Highlights: We examined the effects of noise exposure of other people on noise tolerability. We modeled noise tolerability by adopting reference point of prospect theory. We developed a questionnaire with a hypothetical setting to assess the effects. We conducted face-to-face interviews with residents living near Manila Airport. Residents tolerated more noise when considering people more affected by noise. Abstract: Reactions to aircraft noise resulting from an airport development vary considerably among individuals. This paper examines whether the noise level tolerated by individuals is affected when they compare their own situation to the situations of other people who are more severely affected by the noise. We modeled the individual noise tolerability by adopting the reference point concept and the value function of prospect theory. A questionnaire assessed different levels of noise-affected zones at a hypothetical airport. Individual noise tolerable level was measured by a prerecorded aircraft noise presented via headphones. Decision-making associated with the reported satisfaction level regarding the changes in operational flight frequency settings at the airport. An interview survey was conducted with residents near Manila airport in the Philippines. We applied genetic algorithm to jointly estimate the parameters for noise tolerability model and the value function. Results showed that individuals tolerated more overhead flights when they considered the situations of other people worse affected by the noise than they were. The tendency of noise tolerability increased with the severity of noise exposure situations of other people, but lower reactions to noise escalation. We also observed diminishing sensitivity to changes in noise relative to the noise tolerable level. The aircraft noise tolerability and the consideration of noise exposure situations of other people appeared to be a vital aspect to be considered in airport noise management and policy.